2017
DOI: 10.3892/mmr.2017.6456
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin protects against diabetic cardiomyopathy through NF-κB/AKT/IRS1 in a rat model of type 2 diabetes

Abstract: Troxerutin is a bioflavonoid, which can be used to treat venous disorders, thrombosis and cerebrovascular diseases. Recent studies have demonstrated that it may also be used to prevent edemas. However, it is not known whether troxerutin protects against the cardiomyopathic complications of diabetes. In the present study, a rat model of type 2 diabetes was used to investigate the potential for troxerutin to protect against diabetic cardiomyopathy, through changes to nuclear factor-κB (NF-κB) expression. Troxeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…In vivo, Taxifolin attenuated the structure and function abnormalities by blocking NADPH oxidative activities. Troxerutin ( Figure 5(h) ), a bioflavonoid, protects against DCM through suppression of NF- κ B and JNK in a diabetic rat [ 93 ]. Hesperidin, a flavonoid isolated from citrus, has been shown to reduce oxidative stress and apoptosis and attenuate myocardial injury in isoproterenol-STZ rat via activation of PPAR- γ [ 94 ].…”
Section: Herbal Medicines: Promising Therapeutic For Dcmmentioning
confidence: 99%
“…In vivo, Taxifolin attenuated the structure and function abnormalities by blocking NADPH oxidative activities. Troxerutin ( Figure 5(h) ), a bioflavonoid, protects against DCM through suppression of NF- κ B and JNK in a diabetic rat [ 93 ]. Hesperidin, a flavonoid isolated from citrus, has been shown to reduce oxidative stress and apoptosis and attenuate myocardial injury in isoproterenol-STZ rat via activation of PPAR- γ [ 94 ].…”
Section: Herbal Medicines: Promising Therapeutic For Dcmmentioning
confidence: 99%
“…Researches over the past decades have revealed that TX can act againstγ-radiation-induced lipid peroxidation, UV radiation and colon carcinogenesis[ 28 30 ]. Furthermore, TX can cure retinopathy and play a significant role in the management of type-2 diabetes mellitus[ 31 33 ]. Beside, TX can inhibit 2-AA + UVA radiation-induced DNA damage and environmental carcinogens, showing its potential therapeutic activities for cancer[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…84) Many studies have shown that rutin alleviated DCM and improved cardiac function in animal models of both T1DM and T2DM. [85][86][87][88][89][90] Mechanistically, the protective effects of rutin on DCM are associated with the reduction of oxidative stress, apoptosis, and inflammation. 85) Myricitin: Myricetin is a widely distributed flavonol compound found in many plants, including tea, berries, fruits, vegetables, wines, and medicinal herbs.…”
Section: Beneficial Effects Of Nrf2 Activators On Dcmmentioning
confidence: 99%